1998
DOI: 10.1177/000331979804901206
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Immunodeficiency Virus in Primary Pulmonary Hypertension

Abstract: Previous cases of pulmonary hypertension (PH) in human immunodeficiency virus (HIV) infection have been reported in the literature. The role of HIV in PH is still debatable. The purpose of this report was to analyze whether HIV plays a direct or indirect role in PH pathogenesis. Between February and November 1997, 56 HIV-infected patients with cardiac symptoms and signs were studied by serial color Doppler echocardiography. In four patients (7.1%), PH not related to other well-known associated conditions, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 19 publications
0
37
0
1
Order By: Relevance
“…This indicated that some standard antiretroviral therapy, in particular firstgeneration HIV protease inhibitors but also some HAART treatment, may facilitate the pulmonary vascular pathophenotype of HIV-associated PAH. 103 The mechanism underlying the relationship between ritonavir and pulmonary hypertension is incompletely characterized; however, ritonavir inhibits bradkykinin-dependent vasorelaxation in a concentration-dependent manner leading to endothelial dysfunction. 102 In fact, 5 HAART drugs (ritonavir, indinavir, lamivudine, abacavir, and zidovudine) have been shown to decrease endothelial nitric oxide synthase expression significantly and increase reactive oxygen species levels and ERK1/2 activation in human pulmonary artery endothelial cells in vitro.…”
Section: The Effect Of Antiretroviral Therapy On Pulmonary Arterial Hmentioning
confidence: 99%
“…This indicated that some standard antiretroviral therapy, in particular firstgeneration HIV protease inhibitors but also some HAART treatment, may facilitate the pulmonary vascular pathophenotype of HIV-associated PAH. 103 The mechanism underlying the relationship between ritonavir and pulmonary hypertension is incompletely characterized; however, ritonavir inhibits bradkykinin-dependent vasorelaxation in a concentration-dependent manner leading to endothelial dysfunction. 102 In fact, 5 HAART drugs (ritonavir, indinavir, lamivudine, abacavir, and zidovudine) have been shown to decrease endothelial nitric oxide synthase expression significantly and increase reactive oxygen species levels and ERK1/2 activation in human pulmonary artery endothelial cells in vitro.…”
Section: The Effect Of Antiretroviral Therapy On Pulmonary Arterial Hmentioning
confidence: 99%
“…De todos modos, es importante señalar que los pacientes con hipertensión pulmonar asociada a la infección por el VIH tienen un tiempo de supervivencia menor en comparación con aquellos que no tienen esta condición (1,3 años versus 2,6 años) (2,8.9) . Se ha estimado que ocurre en casi el 0,5% de pacientes hospitalizados y es una causa de compromiso cardíaco severo con cor pulmonale y muerte asociados (2,(8)(9)(10) .…”
Section: Disfunción Ventricular Derecha E Hipertensión Pulmonarunclassified
“…Its prevalence is 1/200 cases, compared with 1/ 200,000 cases in the general population [46][47][48][49][50] . Its detection is often associated with pulmonary infections, use of intravenous drugs, transfusion of factor VIII to hemophilic patients, venous thromboembolism, heart failure and the presence of HLA-DR6 and HLA-DR52 46,47 . It affects approximately 0.5% of hospitalized patients with AIDS.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…It is suggested that HIV itself causes endothelial injury and release of vasoconstrictive mediators such as endothelin-1, interleukin-6 (IL-6), and the tumor necrosis factor alpha in the pulmonary arteries. HIV is often identified in the alveolar macrophages in histological tets 47 . These macrophages release TNF-α, free radicals and proteolytic enzymes in response to the infection.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation